Pengaruh Pembelajaran Daring Berbantuan Video Pembelajaran untuk Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam dimoderasi Motivasi Belajar Siswa - Ahmadi Ahmadi (JURNAL NALAR PENDIDIKAN, 2022)
This study is conducted with the aim of determining the effect of Zakat videos assisted online learning in encouraging class VI student learning to improve learning outcomes of Islamic religious education subjects. Experimental design is used in this study utilizing control and experimental groups.iencing parenting problems, 3) having children experiencing developmental delays, 4) willing to follow the training program. The subjects of this study are class VI children with a total of 30 people. Sampling technique used in this study uses non-probability sampling. The data is collected related to learning outcomes using observation and assessment sheets, while data collection related to student motivation uses questionnaires. The tests used in this study include instrument validity and reliability tests, classical assumption tests, homogeneity tests, and hypothesis testing using Two Way Anova parametric statistics. Distance learning assisted by video learning needs to be carried out continuously in order to improve student learning outcomes. So it would be better if distance learning assisted by learning videos moderated with student motivation was carried out massively and creative innovations were given to improve student learning outcomes to the maximum.